Alpha mangostin Inhibits Hepatic Stellate Cells Activation Through TGF-β/Smad and Akt Signaling Pathways: An in vitro Study in LX2 - Rahmaniah, Rahmaniah; Yuyuntia, Yuyuntia; Soetikno, Vivian; Arozal, Wawaimuli; Antarianto, Radiana Dhewayani; Louisa, Melva (Drug Research, 2018)
Background Alpha mangostin has been reported to have activity for the treatment of liver fibrosis in the rats. However, the mechanisms of action are poorly understood. This study was aimed to investigate the effect of alpha mangostin on hepatic stellate cells (HSC) activation and proliferation through TGF-β/Smad and Akt signaling pathways.Methods Immortalized HSC, LX2 cells, were incubated with TGF-β with or without alpha mangostin (5 or 10 μM). Sorafenib 10 µM was used as positive control. LX2 viability was counted using trypan blue exclusion method. The effect of alpha mangostin on TGF-β concentrations, and the expressions of proliferation and fibrogenic markers were evaluated.Results Alpha mangostin treatment resulted in a reduced proliferation of HSC, decreased Ki-67 and p-Akt expressions. These findings were followed with decreased concentrations of TGF-β in the medium of cells treated with alpha mangostin, decreased expressions of COL1A1, TIMP1, PAI1, α-SMA, and p-Smad3 as fibrogenic markers. These effects were shown to be dose-dependent.Conclusions Alpha mangostin inhibits hepatic stellate cells proliferation and activation through TGF-β/Smad and Akt signaling pathways in dose dependent manner.
Keywords: Alpha mangostin; hepatic stellate cells; TGF-β; Smad; Akt